CollabVR: VR Testing for Increasing Social Interaction between College Students - Johnson, Diego (2024)
The impact of the COVID-19 pandemic on education has accelerated the shift in learning paradigms toward synchronous and asynchronous online approaches, significantly reducing students’ social interactions. This study introduces CollabVR, as a social virtual reality (SVR) platform designed to improve social interaction among remote university students through extracurricular activities (ECAs). Leveraging technologies such as Unity3D for the development of the SVR environment, Photon Unity Networking for real-time participant connection, Oculus Quest 2 for immersive virtual reality experience, and AWS for efficient and scalable system performance, it aims to mitigate this social interaction deficit. The platform was tested using the sociability scale of Kreijns et al., comparing it with traditional online platforms. Results from a focus group in Lima, Peru, with students participating in online ECAs, demonstrated that CollabVR significantly improved participants perceived social interaction, with a mean of 4.65 ± 0.49 compared to traditional platforms with a mean of 2.35 ± 0.75, fostering a sense of community and improving communication. The study highlights the potential of CollabVR as a powerful tool to overcome socialization challenges in virtual learning environments, suggesting a more immersive and engaging approach to distance education.